2018
DOI: 10.23851/mjs.v28i3.60
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some chemical and physical elicitors on some secondary compound induction of Ricinus communis through callus induction

Abstract: The results of the present study showed that AgNO 3 and ABA has a negative effect on fresh and dry weight, where both of weight significantly decreased when treated with ABA and AgNO 3 compare to control treatment, except callus treated with AgNO 3 at 4mg/l, the rate of fresh and dry weight significantly increased reached to 434,77mg respectively compared to control. Physical treatment also had a significant effect on fresh and dry weight for callus, the highest fresh and dry weight significantly reached to 49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, plant tissues respond differently to the applied photoperiod (Siddique & Islam, 2018). According to Twaij & Taha (2017), sequential light periods led to an enhanced fresh and dry weight of callus tissue compared to constant light or dark conditions in Ricinus communis culture. An increase in different phytochemicals was recorded in various cultures of plants (Victório et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, plant tissues respond differently to the applied photoperiod (Siddique & Islam, 2018). According to Twaij & Taha (2017), sequential light periods led to an enhanced fresh and dry weight of callus tissue compared to constant light or dark conditions in Ricinus communis culture. An increase in different phytochemicals was recorded in various cultures of plants (Victório et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Conclusively, many previous studies have demonstrated the efficiency of using light as a physical abiotic factor in stimulating the biosynthesis of primary and secondary plant compounds through increased activity of the phenylalanine ammonia-lyase (PAL) enzyme (Abbasi et al, 2007), enhancement of chlorophyll biosynthesis and regulation of gene expression responsible for the synthesis of terpenes (Kawoosa et al, 2010), improvement of the accumulation of phenolic and flavonoids contents (Adil et al, 2019a) and formation of anthocyanins and carotene pigments (Li & Kubota, 2009). According to Twaij & Taha (2017), the incubation of callus culture of Ricinus communis under continuous light conditions was more effective for the stimulation of quercetin, kaempferol and ricinin compounds. In Eclipta alba callus culture, the long light periods also induce the biosynthesis of several secondary metabolites (Khurshid et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier research findings have observed variations in the impact of light on the promotion of callus growth. Specifically, in the plants Citrullus colocynthisin (17) and Ricinus communis (18), it was found that regular light cycles consisting of 16 hours of light followed by 8 hours of darkness resulted in a greater increase in the mass of callus tissue (both fresh and dry weight) compared to continuous exposure to either light or darkness.…”
Section: Discussionmentioning
confidence: 99%